Mitigating Ischemia-Reperfusion Injury Using a Bilobed Partial REBOA Catheter: Controlled Lower-Body Hypotension. Issue 3 (March 2021) - Necsoiu, Corina; Jordan, Bryan S.; Choi, Jae H.; Moon, James J.; Espinoza, Mark D.; Gremmer, Brandon J.; Batchinsky, Andriy I.; Cancio, Leopoldo C.
ABSTRACT: Background: Non-compressible torso hemorrhage (NCTH) is the leading cause of potentially preventable death on the battlefield. Resuscitative endovascular balloon occlusion of the aorta (REBOA) aims to restore central blood pressure and control NCTH below the balloon, but risks ischemia-reperfusion injury to distal organs when prolonged. We tested a bilobed partial REBOA catheter (pREBOA), which permits some of the blood to flow past the balloon. Methods: Female swine (n = 37, 6 groups, n = 5–8/group), anesthetized and instrumented, were exponentially hemorrhaged 50% of estimated blood volume (all except time controls [TC]). Negative controls (NC) did not receive REBOA or resuscitation. Positive controls (PC) received retransfusion after 120 min. REBOA groups received REBOA for 120 min, then retransfusion. Balloon was fully inflated in the full REBOA group (FR), and was partially inflated in partial REBOA groups (P45 and P60) to achieve a distal systolic blood pressure of 45 mm Hg or 60 mm Hg. Results: Aortic occlusion restored baseline values of proximal mean arterial pressure, cardiac output, and carotid flow in pREBOA groups. Lactate reached high values during occlusion in all REBOA groups (9.9 ± 4.2, 8.0 ± 4.1, and 10.7 ± 2.9 for P45, P60, and FR), but normalized by 6 to 12 h post-deflation in the partial groups. All TC and P60 animals survived 24 h. The NC, PC, and P45 groups survived 18.2 ± 9.5, 19.3 ± 10.6, and 21.0 ± 8.4 h. For FR animals mean survival was 6.2 ± 5.8 h, significantly worse than all other animals ( P < 0.01, logrank test). Conclusions: In this porcine model of hemorrhagic shock, animals undergoing partial REBOA for 120 min survived longer than those undergoing full occlusion. Abstract : Supplemental Digital Content is available in the text